2006
DOI: 10.1196/annals.1372.023
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the Different Neuropeptide‐Containing Nerve Fibers and Immunocells in the Diabetic Rat's Alimentary Tract

Abstract: Peripheral neuropathy is a common complication of diabetes mellitus, where neuropeptides and immunocells might play important roles in the pathogenesis of the disease. In this article we have quantified the different neuropeptide-containing nerve fibers and immunocells in the streptozotocin-induced diabetic rat's alimentary tract (tongue, duodenum, colon) using immunohistochemical and immunocytochemical methods. The immunoreactive (IR) nerve fibers were found in all layers of the alimentary tract and their dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 71 publications
(108 reference statements)
0
8
0
5
Order By: Relevance
“…Substance P has also shown variable results in diabetic animal models. In streptozotocin-induced rats, the number of duodenal substance P reactive nerve fibers increased after 4 weeks (Feher et al 2006), while a study of longer duration (10 weeks) showed a reduction of substance P total content in stomach and small intestine (Ballman and Conlon 1985). Interestingly, a study looking at the small intestine and stomach during prolonged (12–18 month) streptozotocin-induced diabetes showed no change in substance P innervation between diabetic and control rats (Schmidt et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Substance P has also shown variable results in diabetic animal models. In streptozotocin-induced rats, the number of duodenal substance P reactive nerve fibers increased after 4 weeks (Feher et al 2006), while a study of longer duration (10 weeks) showed a reduction of substance P total content in stomach and small intestine (Ballman and Conlon 1985). Interestingly, a study looking at the small intestine and stomach during prolonged (12–18 month) streptozotocin-induced diabetes showed no change in substance P innervation between diabetic and control rats (Schmidt et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…NPY, another inhibitory neurotransmitter, present predominantly in NANC neurons, often co‐localizes with nNOS 26 . Increase in NPY immunoreactivity in duodenum, colon and ileum has been reported in rats 25,27 . Obese diabetic mice also show increased NPY in the colon 28 .…”
Section: Diabetes and Neuronal Degenerationmentioning
confidence: 97%
“…Decrease in SP in stomach and ileum of rats at varied durations of 5–44 weeks of diabetes has also been reported. Although some studies demonstrate an increase in SP, 18,27 a majority of studies support a reduction in SP in diabetes 37,38 . Recent findings indicate that autoimmune attack on β‐cells as in diabetes type I appears to be triggered by abnormal sensory nerves that lack SP 39 .…”
Section: Diabetes and Neuronal Degenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ezáltal befolyá-solja a különböző immunsejtek válaszát, például lymphocyták proliferációját, az NK-sejtek citotoxicitását, a különböző citokinek és antitestek termelését [1,2]. Az idegrostok mennyisége is megváltozik különböző gyulladásos folyamatokban és autoimmun betegségekben [3,4]. A legutóbbi irodalmi adatok számos zsigerben igazolták a neuropeptid IR idegrostok és immunkompetens sejtek szoros kapcsolatát, ami az ideg-és immunrendszer között meglévő kölcsönös egymásra hatás morfológiai bizonyítéka.…”
Section: öSszefoglaló Közleményunclassified